La educación de personas adultas en la sociedad de la información - Ramón Flecha; Carmen Elboj (Universidad Nacional de Educación a Distancia (UNED), 2000)
This article introduces an analysis ofthe challenges adult education faces in the context ofthe Information society from the critical pedagogy and the communicative research approaches developed by CREA (Centre for Social and Educational Research). In the first parí, these approaches are placed within the current social, labour and educational context and in relation to the contributions ofdifferent authors from the social sciencies. The second parí, introduces research and concrete experiencies in order to clarify the evolution ofthe field of adult education. Furíhermore, it highlights the importance offacilitating access to new technologies for all the people, as a mechanism to avoid new social inequalities and to overeóme those that already exist. From the reference of two projects, Distance and Omnia, we compile those practices and educational methodologies that foster and democratise the new technologies extensión and education through them, for all. The organization ofthe educational model we propose for the twenty first century is three-fold: a) participants b) educators and c) University professors who are involved in the scientific community